Principles of construction of nanosatellite radar systems based on global navigation satellite system reflectometry - A. V. Ksendzuk; V. F. Fateev (Российский технологический журнал, 2024)
Objectives. The development of radar remote sensing systems based on the reception of signals of navigation satellite systems reflected from the surface enables a constellation of nanosatellites to be deployed, in order to perform radar surveying of the Earth’s surface. The aim of this work is to develop the principles of construction of onboard bistatic remote sensing systems on nanosatellites, in order to assess the energy potential and possibilities for its increase.Methods. The optimal processing method in onboard bistatic radar systems is a development of known analytical methods of optimal processing in monostatic systems. The calculation of the energy potential is based on the experimental data obtained by other authors.Results. The utilization of signals from navigation satellite systems for surface sensing is a promising and developing area. The USA and China have deployed satellite constellations to perform remote sensing using reflected signals of navigation satellites. An algorithm for optimal processing in such systems, which realizes the principle of aperture synthesis, was developed, and the energy potential of bistatic synthetic aperture radar was calculated. In order to achieve this processing, the proposed scheme uses a standard navigation receiver to form reference signals.Conclusions. The application of optimal processing methods in bistatic radar enables a synthetic aperture based on scattered satellite navigation system signals. In order to improve the accuracy of estimates, the signal-to-noise ratio needs to be increased by combining coherent accumulation (aperture synthesis) and incoherent accumulation (aggregating measurements from different spacecraft). The signal processing methods and receiver structure proposed in this work onboard nanosatellites allow aperture synthesis to be achieved with realizable hardware requirements.